THE ROLE OF AGRICULTURAL EMPLOYEES IN THE OPERATION OF AGRICULTURAL TECHNOLOGIES TRANSFER TO FARMERS IN NINEVEH GOVERNORATE - AHMED ALTALB; Marwa A. S. AL-Zubaidi (Mesopotamia Journal of Agriculture)
The present research aims at identifying the role of agricultural employees in the operation of agricultural technologies transfer to farmers in Nineveh Governorate in general, and in each field of the research fields،which included (organization field, planning field، implementation field، follow-up field, evaluation field). The comparison between the role of agricultural employees at the centers of the Directorate of Agriculture of Nineveh and its agricultural divisions in the transfer of agricultural technologies. Light is shed on the relation between the role of the officials un the transfer of the technologies and the following independent variables (age, educational level, specialization، origin, duration of service in agricultural departments، sources of agricultural information).The research included all  the agricultural employees in the Directorate of Agriculture Nineveh and its affiliated sections which are (384) agricultural workers, a random sample (60%)  has been selected (231) agricultural employees، (89) agricultural employees from  the sections  of Nineveh Agriculture Directorate, (142) agricultural employees distributed to the agricultural divisions in the Directorate of Agriculture Nineveh، (30) employees have been excluded because they are  included in  measuring the validity  of the research. A questionnaire has been prepared which included (75) paragraphs to measure the role of agricultural employees distributed in five areas related to programs for the transfer of agricultural technologies concerning organization ، planning، implementation, follow-up and maintenance. Each field has a number of paragraphs (11, 16, 19, 13, 16), respectively, with a five-point scale including the following expressions: (I have a very big role, I have a big role، I have an average role, I have little role, I have no role). The following numerical values have beengiven (5,4,3,2,1) respectively. The results showed that the role of agricultural employees in the transfer of agricultural technology in general was average and tends to increase, which indicates the role of agricultural employees. It recommended that training courses be undertaken to provide agricultural employees with the necessary information and expertise to improve their role in agricultural technology transfer programs.